PENGARUH AIR SODA TERHADAP KUAT TEKAN BETON - SURYA HADI (Universitas Mahasaraswati K. Mataram, 2021)
Many research regarding concrete were conducted especially in order to enhance the strength, whether using additional materials or other substitutional materials. Of many research in order to enhance concrete compression strength, there were still any weaknesses found. This study aimed to investigate the effect of soda water used to partly substitute the water mixture towards concrete compression strength. This study used 0,6,7,8,9 and 10 % of soda water with six experimental objects for each and the total of experimental objects used were 36 objects. The conclusion taken from the experiment of the objects for 28 days was that by adding water soda from 6 % until 10 % could significantly improve the concrete compression strength. 8% water soda adding was the maximum point of compression strength. After the adding of water soda more than 8 %, compression strength decreased but still above the limits of normal concrete compression strength